Group A streptococcal disease in paediatric inpatients: a European perspective. - Boeddha, Navin P.; Atkins, Lucy; de Groot, Ronald; Driessen, Gertjan; Hazelzet, Jan; Zenz, Werner; Carrol, Enitan D.; Anderson, Suzanne T.; Martinon-Torres, Federico; Agyeman, Philipp K.A.; Galassini, Rachel; Herberg, Jethro; et al. (European Journal of Pediatrics, 2023)
UNLABELLED: Group A streptococcal (GAS) disease shows increasing incidence worldwide. We characterised children admitted with GAS infection to European hospitals and studied risk factors for severity and disability. This is a prospective, multicentre, cohort study (embedded in EUCLIDS and the Swiss Pediatric Sepsis Study) including 320 children, aged 1 month to 18 years, admitted with GAS infection to 41 hospitals in 6 European countries from 2012 to 2016. Demographic, clinical, microbiological and outcome data were collected. A total of 195 (61%) patients had sepsis. Two hundred thirty-six (74%) patients had GAS detected from a normally sterile site. The most common infection sites were the lower respiratory tract (LRTI) (22%), skin and soft tissue (SSTI) (23%) and bone and joint (19%). Compared to patients not admitted to PICU, patients admitted to PICU more commonly had LRTI (39 vs 8%), infection without a focus (22 vs 8%) and intracranial infection (9 vs 3%); less commonly had SSTI and bone and joint infections (p < 0.001); and were younger (median 40 (IQR 21-83) vs 56 (IQR 36-85) months, p = 0.01). Six PICU patients (2%) died. Sequelae at discharge from hospital were largely limited to patients admitted to PICU (29 vs 3%, p < 0.001; 12% overall) and included neurodisability, amputation, skin grafts, hearing loss and need for surgery. More patients were recruited in winter and spring (p < 0.001). CONCLUSION: In an era of observed marked reduction in vaccine-preventable infections, GAS infection requiring hospital admission is still associated with significant severe disease in younger children, and short- and long-term morbidity. Further advances are required in the prevention and early recognition of GAS disease. WHAT IS KNOWN: • Despite temporal and geographical variability, there is an increase of incidence of infection with group A streptococci. However, data on the epidemiology of group A streptococcal infections in European children is limited. WHAT IS NEW: • In a large, prospective cohort of children with community-acquired bacterial infection requiring hospitalisation in Europe, GAS was the most frequent pathogen, with 12% disability at discharge, and 2% mortality in patients with GAS infection. • In children with GAS sepsis, IVIG was used in only 4.6% of patients and clindamycin in 29% of patients.
EVALuna2:551736